Finite larmor radius effects on turbulent transport of test-particles - Cherniak, O.M.; Zasenko, V.I.; Zagorodny, A.G. (Вопросы атомной науки и техники, 2016)
A test-particle approach to study transport processes in two-dimensional random electric field is proposed. Despite such approach is not as complete as self-consistent one it allows a better control of problem parameters and makes results more tractable. A frozen electric field is considered. Because of a strong particle trapping effect the problem is a difficult test for statistical methods. Earlier in our previous works particle transport was examined in a drift approximation; here we study finite Larmor radius effects on particle transport. Some methods to account for a finite Larmor radius are considered as generalization of our moment approximation. Results of analytical approximations and direct numerical simulation are compared, and most accurate method is found. The difference between dispersion of particle and gyrocentre displacement is discussed.